Correction: Reduced crossover interference and increased ZMM-independent recombination in the absence of Tel1/ATM. - Carol M Anderson; Ashwini Oke; Phoebe Yam; Tangna Zhuge; Jennifer C Fung (PLoS Genetics, 2025)
[This corrects the article DOI: 10.1371/journal.pgen.1005478.].